Suitability of Mikania mikrantha H.B.K. for Papermaking - Guha, S. R. D.; Dhoundiyal, S. N.; Sekhar, Jainagesh A. (Indian Forester, 1974)
The paper reports results of an investigation on tbe suitability of Mikaina micrantha for papermaking. Chemical pulps were obtained only in low yields and with low strength properties.